Evaluation of perceived stress and its correlation with personality traits in undergraduate students - Shanmukha Varalakshmi Vangara; Anita Kumari; Dhananjay Kumar (Asian Journal of Medical Sciences, 2022)
Background: Stress is a normal psychological, physiological, and behavioral response of any individual. It is the struggle of an individual to cope up with the situation doing more than one’s ability. It can lead to ill health over a period of time, if ignored. Personality refers to one’s behavior toward the environment and oneself. Stress can regulate personality of an individual. It may create great impact on their educational and emotional behavior in student’s life. It is essential to identify and counsel the students undergoing excessive stress and having negative personality. Aims and Objectives: The aim of this study is to evaluate perceived stress and correlate it with personality traits in undergraduate students. (i) To evaluate perceived stress in undergraduate students using Perceived Stress Scale (ii) To evaluate personality traits using Eysenck Personality Inventory Scale (iii) To classify students having different personality traits (iv) To correlate perceived stress levels with different personality traits. Materials and Methods: This study evaluates perceived stress and personality in 130 nursing and paramedical students attending a corporate college. Two scales – EPI scale proposed and PSS were used. Mean, standard deviation, and Pearson’s correlation were calculated to determine the relationship between personality traits and perceived stress. Results: Mean values of neuroticism, extraversion, and lie score are greater in males than in females. Females had statistically significant higher mean stress values than males. Majority of the students were under moderate stress with 72.6% and 81.1% among male and female subjects, respectively. On comparison, percentage of neuroticism cases was higher in females (49.1%) than males (35.6%). More introvert percentages were found in male subjects compared to females. More ambivert percentages were noted in females than in males. Percentage reliability was greater in females compared to males. Conclusion: This study reveals that higher the neurotic factor greater is the perceived stress and higher the values of extraversion lower are the perceived stress values. Gender differences were noticeable in perceived stress. Hence, the aspect of counseling can be adopted accordingly to understand the psychology of the fresher’s and modulate their mind set to help them cope with academic and personal life situations in an efficient way.